2016
DOI: 10.1080/10590501.2015.1135593
|View full text |Cite
|
Sign up to set email alerts
|

7-cysteine-pyrrole conjugate: A new potential DNA reactive metabolite of pyrrolizidine alkaloids

Abstract: Pyrrolizidine alkaloids (PAs) require metabolic activation to exert cytotoxicity, genotoxicity, and tumorigenicity. We previously reported that (±)-6,7-dihydro-7-hydroxy-1-hydroxymethyl-5H-pyrrolizine (DHP)-derived DNA adducts are responsible for PA-induced liver tumor formation in rats. In this study, we determined that metabolism of riddelliine and monocrotaline by human or rat liver microsomes produced 7-cysteine-DHP and DHP. The metabolism of 7-glutathionyl-DHP by human and rat liver microsomes also genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 28 publications
3
39
0
Order By: Relevance
“…It is generally accepted that PAs themselves are biologically inactive and require metabolic activation to exert their toxic effects (Chen et al 2016 ; Fashe et al 2015 ; Fu et al 2004 ; He et al 2016 ; Mattocks 1986 ; Mei et al 2010 ; Roeder 2000 ; Wiedenfeld and Edgar 2011 ). The non-toxic metabolites are quickly excreted, while the metabolically mediated toxification process is thought to include an oxidation to yield the corresponding dehydropyrrolizidine (pyrrolic ester) derivatives (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…It is generally accepted that PAs themselves are biologically inactive and require metabolic activation to exert their toxic effects (Chen et al 2016 ; Fashe et al 2015 ; Fu et al 2004 ; He et al 2016 ; Mattocks 1986 ; Mei et al 2010 ; Roeder 2000 ; Wiedenfeld and Edgar 2011 ). The non-toxic metabolites are quickly excreted, while the metabolically mediated toxification process is thought to include an oxidation to yield the corresponding dehydropyrrolizidine (pyrrolic ester) derivatives (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Further study identified pyrrole-lysine adducts in PA-treated mice, which supported the formation of PPAs in vivo (Li et al 2016). Other proteinogenic amino acids, such as cysteine, valine, and histidine were further found to be capable of binding to the pyrrole moiety through chemical synthesis in the in vitro or in vivo models (Estep et al 1990;He et al 2016aHe et al , b, 2017Ma et al 2019;Xia et al 2015;Zhao et al 2014). All these results support that both DHPAs and DHP possessing bi-functional electrophilic substituents at C7 and C9 positions of the core pyrrole moiety are capable of alkylating to the nucleophilic sites at the -SH and -NH functional groups of the target proteins, leading to the formation of PPAs (Fig.…”
Section: Formation Of Pyrrole-protein Adductsmentioning
confidence: 82%
“…Although DHP is less reactive than DHPAs, it retains considerable alkylating activity and is also capable of reacting with DNA and form PDAs but to a much lesser extent compared to DHPAs (Fu et al 2004;Wang et al 2005b). In the recent studies using in vitro models, Fu et al reported a series of synthetic secondary PA metabolites, including pyrrole-7-GSH conjugate (7-GSH-DHP), pyrrole-7-cysteine conjugate (7-CYS-DHP), pyrrole-7-N-acetylcysteine conjugate (7-acetyl-CYS-DHP), and 1-formyl-7-hydroxy-6,7-dihydro-5H-pyrrolizine (1-CHO-DHP) and found that all these secondary PA metabolites possessed DNA-binding activity and formed PDAs when incubated with calf thymus DNA (He et al 2017(He et al , 2016aXia et al 2015Xia et al , 2018) (Fig. 5).…”
Section: Formation Of Pyrrole-dna Adductsmentioning
confidence: 99%
“…Following PA ingestion, metabolic activation is initiated by catalysis in the liver by cytochrome P450 monooxygenases, and the generated metabolite can rapidly combine with cellular DNA, proteins, or glutathione to form the corresponding adducts. [12][13][14] The formation of protein adducts may impair the biological function of the target protein or activate immune responses, leading to toxicity. 15 However, because of the diverse array of potential pyrrole-protein adducts, the specific target proteins and binding sites have not been fully identified.…”
Section: Discussionmentioning
confidence: 99%